Exploring the Intersection of Body Dysmorphic Disorder (BDD) and Dermatological Conditions: A Narrative Review - Vivian Li; Kelly Frasier; Emily Woolhiser; Kathleen Daly; Sara Christoforides; Courtnee Harpine; Karina Stech; Stefany Acosta; Edwin D. Lephart (Adis, Springer Healthcare, 2024)
Abstract This narrative literature review examined the intricate relationship between body dysmorphic disorder (BDD) and dermatological conditions, with a brief focus on those characterized by conspicuous skin irregularities such as acne vulgaris, psoriasis, and vitiligo. Highlighting the significant prevalence of BDD among individuals afflicted with dermatological issues, our analysis illuminated the profound psychological repercussions stemming from an exaggerated preoccupation with perceived skin imperfections. Through an exploration of the underlying BDD symptoms, we analyzed the complex dynamics between skin health and mental well-being, emphasizing the disorder's impact on patients' psychological and social functioning. This narrative review further investigated the consequential effects of BDD on essential aspects of dermatological treatment, including patient adherence to therapeutic regimens, overall quality of life (QOL), and the effectiveness of available treatments. In addition to presenting current therapeutic approaches, we advocate for the integration of psycho-dermatological interventions tailored to mitigate the dual burden of skin conditions and psychological distress. Future research directions proposed include longitudinal studies to assess the long-term effects of BDD on skin disease prognosis and psychosocial well-being, which aim to refine and optimize treatment modalities to contribute to a more holistic understanding of BDD within dermatological practice.